Effect of Polyol Synthesis Parameters on Particle Size and Crystal Size of ZnO: A Systematic Review - Kormil Saputra; Rizka Ayu Fitri; Dian Wijaya Kurniawidi (MASALIQ, 2026)
Zinc oxide nanoparticles (ZnO NPs) are semiconductor oxide materials that have been widely developed because of their high chemical stability, relatively low synthesis cost, and broad potential applications in photocatalysis, sensors, pigments, catalysts, optical materials, and nanofluid systems. Particle size and crystallite size are critical parameters because they directly influence surface area, crystallinity, morphology, charge transfer, and the functional performance of ZnO. This study aims to examine the effects of synthesis parameters in the polyol method on the particle size and crystallite size of ZnO-based nanomaterials through a systematic literature review. Relevant literature published between 2021 and 2026 was collected from Scopus, ScienceDirect, and Google Scholar using Boolean search strategies. The selected articles were screened based on predetermined inclusion and exclusion criteria and analyzed using a descriptive-comparative approach. The review findings indicate that the polyol method influences the morphostructural characteristics of ZnO through several synthesis variables, including the type of polyol, precursor ratio, water content, base concentration, reaction temperature, reaction time, surfactants, stabilizers, and post-synthesis treatment. Ethylene glycol and diethylene glycol tend to support the formation of ZnO with smaller crystallite size and more controlled morphology, whereas prolonged reaction time and high-temperature calcination may increase crystal growth. In addition, doping and the use of surfactants can restrict crystal growth and reduce agglomeration. This review concludes that the polyol method is effective for controlling the particle size and crystallite size of ZnO; however, simultaneous optimization of synthesis parameters is required to obtain ZnO nanomaterials with morphostructural characteristics suitable for functional applications.